Criminology Study on Pedophilia Prevention in Inonesia - Tri Akhmad Aji Saputra; Eko Soponyono (Universitas Ahmad Dahlan, 2018)
Children are frequently victims of misconduct regarding the current widespread sexual abuse perpetrated by elders who are usually known by them, it is called pedophiles. Criminology reviews, therefore, are very crucial to analyze the crime. Pedophilia is a psychiatric disorder in which an adult experiences a primary or exclusive sexual attraction to pre-pubescent children, the cut-off point for pre-pubertal to age 13. The disorder results in sexual abuse, including Nepiophilia or Infantophilia that is sexual attraction to infants under 3 years old. Pedophiles, then, are adults of deviant sexual behavior abusing children. This study is aimed to examine and analyze criminology reviews for prevention of pedophile crime. It is normative juridical approach (statute approach), the conceptual and the comparative one. The factors of committing pedophilia are internal of the personal perpetrator, and external in which the community vastly influences on committing the crime and to shape how someone becomes a bad person or good one. Thus, to overcome the crime is to carry out pre-emptive, preventive, repressive and rehabilitative methods. In addition, one of child protection policies to anticipate child sexual abuse increase including pedophiles, the Government issued a regulation (Perpu) No. 1 of 2016 on the second amendment of Act No. 23 of 2002 of the children protection. The Government Regulation (Perpu) No. 1 then is legislated as Act 17 of 2016. Based on comparative studies of other countries, there is a voluntarily castration in which the perpetrators must be ready to be emasculated, aimed to reduce or suppress their libido. Yet, Indonesia values emphasizing Pancasila (Five Principles) must be referred: just and civilized humanity (humanism).